ANALISIS HASIL BELAJAR MATEMATIKA SISWA KELAS V DI SD NEGERI 2 PURWOKERTO KULON - Kurniawan Pratama, Bagus; Mareza, Lia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the mathematics learning outcomes of grade V students at SD Negeri 2 Purwokerto Kulon and identify the factors that influence their academic achievement. The research method used is a qualitative approach with interview, observation and documentation techniques. The results show that the learning methods used by teachers, students' involvement in learning, as well as students' learning strategies play an important role in math learning outcomes. The main difficulty experienced by students is in understanding the concepts of GCD and division. The use of learning media is still limited, with the majority of students relying on textbooks as the main source. This research highlights the importance of more innovative and interactive learning approaches, including the use of technology in mathematics learning. The findings are expected to provide recommendations for the development of more effective learning strategies to improve student learning outcomes.